1991
DOI: 10.3171/jns.1991.75.1.0056
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the timing of aneurysm surgery and the development of delayed cerebral ischemia

Abstract: A consecutive series of 145 patients with acute aneurysmal subarachnoid hemorrhage (SAH) were operated on within 7 days of SAH and were prospectively evaluated over a 4-year period to determine if the timing of aneurysm surgery influenced the development of delayed cerebral ischemia. All patients were managed with a standardized policy of urgent surgical clipping and treatment with aggressive prophylactic postoperative volume expansion. Patients with delayed ischemic symptoms were additionally treated with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 54 publications
3
38
0
1
Order By: Relevance
“…For example, craniotomy with brain retraction and surgical manipulation of blood vessels may exacerbate preexisting vasospasm. 24,25,27,28 Therefore, although decreasing the clot burden theoretically contributes to lowering the rates of vasospasm, this beneficial effect could be negated by other effects associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, craniotomy with brain retraction and surgical manipulation of blood vessels may exacerbate preexisting vasospasm. 24,25,27,28 Therefore, although decreasing the clot burden theoretically contributes to lowering the rates of vasospasm, this beneficial effect could be negated by other effects associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SPSS software version 19 (SPSS Inc., Chicago, IL, USA) was used to perform statistical analysis. proach such as the timing of treatment and the differences between interventional techniques, and almost all of them referred to surgical series [3][4][5][6][7][8] . Furthermore, a prospective study on a group of patients with ruptured aneurysms treated with surgical clipping demonstrated that early treatment may reduce the risk of rebleeding 9 .…”
Section: Introductionmentioning
confidence: 99%
“…More and more neurosurgeons rely on early aneurysm surgery rather than delayed surgery for the prevention of rebleeding after aneurysmal SAH. [3][4][5][6][7][8][9][10][11][12] The rationale behind early aneurysm surgery is that by clipping the aneurysm as early as possible, one can apply treatment for cerebral ischemia more vigorously (for example, induced hypertension) without the risk of a rebleed. However, in most studies early aneurysm surgery failed to improve outcome when compared with delayed surgery, probably because of an increase in the frequency of cerebral ischemia.…”
mentioning
confidence: 99%